2012
DOI: 10.1371/journal.pone.0051978
|View full text |Cite
|
Sign up to set email alerts
|

Lead Exposure in Bald Eagles from Big Game Hunting, the Continental Implications and Successful Mitigation Efforts

Abstract: Studies suggest hunter discarded viscera of big game animals (i.e., offal) is a source of lead available to scavengers. We investigated the incidence of lead exposure in bald eagles in Wyoming during the big game hunting season, the influx of eagles into our study area during the hunt, the geographic origins of eagles exposed to lead, and the efficacy of using non-lead rifle ammunition to reduce lead in eagles. We tested 81 blood samples from bald eagles before, during and after the big game hunting seasons in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 24 publications
3
82
0
Order By: Relevance
“…Scavenging of unretrieved carcasses or offal left in the field from animals other than waterfowl killed or wounded with lead ammunition has been suggested as the primary pathway for continued lead exposure and poisoning in eagles (Wayland et al 2003;Neumann 2009;Pain et al 2009;Stauber et al 2010;Bedrosian et al 2012;Nadjafzadeh et al 2013). Some of these studies have reported greater lead exposure frequency in eagles in autumn and winter months, linking exposure to time periods during and after hunting seasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scavenging of unretrieved carcasses or offal left in the field from animals other than waterfowl killed or wounded with lead ammunition has been suggested as the primary pathway for continued lead exposure and poisoning in eagles (Wayland et al 2003;Neumann 2009;Pain et al 2009;Stauber et al 2010;Bedrosian et al 2012;Nadjafzadeh et al 2013). Some of these studies have reported greater lead exposure frequency in eagles in autumn and winter months, linking exposure to time periods during and after hunting seasons.…”
Section: Discussionmentioning
confidence: 99%
“…hunting seasons, suggesting an association between lead poisoning in eagles and deer offal left in the field. Large numbers of lead fragments have been found in deer killed with lead rifle ammunition and recent reports have provided additional evidence linking lead exposure of eagles with discarded carcasses and offal (Hunt et al 2006;Neumann 2009;Bedrosian et al 2012;CruzMartinez et al 2012;Warner et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, unlike osprey, bald eagles show strong seasonal variation in diet and during winter they scavenge frequently, often on remains of hunter-killed deer (Wilmers et al 2003;Bedrosian et al 2012). It seems reasonable to conclude, therefore, that the differences in blood lead levels of free-flying birds of the 2 species must be due to behaviors during the nonbreeding season.…”
Section: Potential Sources Of Exposurementioning
confidence: 99%
“…The number of articles per year showed a strong increase over time during the period covered: 6.9 in 1975–1989, 9.3 in 1990–1999, 19.0 in 2000–2009, and 27.7 in 2010–2016. These papers were analyzed for relevance and conclusions, with special reference to topics such as health risks for humans consuming game hunted with lead-based ammunition (e.g., Johansen et al 2004), lead residues in game meat intended for human consumption (e.g., Andreotti et al 2016), use of apex species as biomonitoring sentinels for lead exposure and effects (e.g., Mateo-Tomás et al 2016), lead poisoning of critically endangered species (e.g., Bakker et al 2016), scavengers (Bedrosian et al 2012), upland game birds (e.g., Kreager et al 2008), and waterfowl (e.g., Green and Pain 2016), lead fragments in carcasses and offal (Cruz-Martinez et al 2015), and lead contamination from shooting ranges (Okkenhaug et al 2016). We found that more than 99% of them raised concerns over use of lead-based ammunition.…”
mentioning
confidence: 99%